Risk factors for shiga toxin-producing Escherichia coli-associated human diseases - Rivas, Marta; Chinen, Isabel; Miliwebsky, Elizabeth; Masana, Marcelo Oscar (American Society for Microbiology, 2019)
We have reviewed the risk factors for the occurrence of Shiga toxin-producing Escherichia coli (STEC)-associated human diseases. The analysis of STEC surveillance data and trends shows differences in frequency and severity of the illnesses across countries, whereas the economic and social costs for the affected families, the community, and the health system are better estimated in developed countries. The occurrence of STEC infections is determined by the interaction of the pathogen, the reservoirs, and the biological, cultural, and behavioral aspects of the host. The main risk factors identified in earlier case-control and population-based studies were dietary behaviors and beef consumption. However, in recent years, other risky exposures have also emerged, like the consumption of raw vegetables and sprouts, working or camping in rural areas, visiting farms, and person-to-person transmission. Epidemiological changes have also been determined by the intensification of cattle production, the increase in centralized food production and distribution, and the growth in the volume of international trade of foods. The main lessons learned from recent large outbreaks are knowledge of virulence determinants of new pathogenic strains, recognition of new vehicles of infection, development of new methodologies for detecting STEC in foods and humans, improvement in food regulations and hygiene guidelines, new therapeutic approaches in the treatment of infected patients, establishment of continuous educational programs for food consumers, and enhanced cooperation and teamwork of regional and international networks.